2016
DOI: 10.1177/0193945916650648
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Promoters to Participation in the Era of Shared Treatment Decision-Making

Abstract: This study aimed to identify the barriers and promoters for participation in cancer treatment decision in the era of shared decision-making (SDM) process. A qualitative design was utilized. Nineteen nurses and 11 nurse practitioners from oncology inpatient and outpatient settings participated in semi-structured interviews. Data were analyzed using directed content analysis. The findings include practice barrier, patient barrier, institutional policy barrier, professional barrier, scope of practice barrier, ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 22 publications
3
32
0
Order By: Relevance
“…Therefore, such decisions require shared decision‐making (SDM), an approach for involving healthcare professionals’ evidence and expertise and patients’ values and preferences in treatment decision‐making (Charles, Gafni, & Whelan, 1997; Elwyn et al., 2017; Stiggelbout, Pieterse, & De Haes, 2015). Given their strong relationship with patients and unique expertise, nurses are increasingly considered important for and complemental to physicians’ role in treatment decision‐making (Buiting, Rurup, Wijsbek, van Zuylen, & den Hartogh, 2011; Elwyn et al., 2012; McCarter et al., 2016; McCullough, McKinlay, Barthow, Moss, & Wise, 2010). Importantly, patients want nurses to be involved (NFK, 2019) and report that nurses are valuable and influential in treatment decision‐making (McCarter et al., 2016; McCullough et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, such decisions require shared decision‐making (SDM), an approach for involving healthcare professionals’ evidence and expertise and patients’ values and preferences in treatment decision‐making (Charles, Gafni, & Whelan, 1997; Elwyn et al., 2017; Stiggelbout, Pieterse, & De Haes, 2015). Given their strong relationship with patients and unique expertise, nurses are increasingly considered important for and complemental to physicians’ role in treatment decision‐making (Buiting, Rurup, Wijsbek, van Zuylen, & den Hartogh, 2011; Elwyn et al., 2012; McCarter et al., 2016; McCullough, McKinlay, Barthow, Moss, & Wise, 2010). Importantly, patients want nurses to be involved (NFK, 2019) and report that nurses are valuable and influential in treatment decision‐making (McCarter et al., 2016; McCullough et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The review found no Brazilian studies, not even among excluded works. Some barriers to shared decision-making are common to many countries, such as time constraints on health care, resistance of health professionals due to the fear of loss of control in their relationship with the patient, and the belief that people do not want to be involved in decision-making about their health or do not have this ability and may make inappropriate decisions, putting themselves at risk, even in the presence of scientific uncertainty 7,21 .…”
Section: Discussionmentioning
confidence: 99%
“…44 The role of nurses is described elsewhere as educating patients about treatments and side effects, advocating on patients' behalf and coaching them in decision making, 12 15 49 50 and nurses are seen as valuable and influential in decision making about life-prolonging treatment. [51][52][53] The tools in the studies all involved written material. It can therefore be expected that their feasibility might be less in populations that might also be underrepresented in the study samples, such as adult migrant groups who are not native speakers of that language or people with limited health literacy.…”
Section: Reviewmentioning
confidence: 99%